Addressing the Need for Just GeoHealth Engagement: Evolving Models for Actionable Research That Transform Communities. (14th December 2021) - Hayhow, Claire M.; Brabander, Dan J.; Jim, Rebecca; Lively, Martin; Filippelli, Gabriel M.
Abstract: GeoHealth as a research paradigm offers the opportunity to re‐evaluate common research engagement models and science training practices. GeoHealth challenges are often wicked problems that require both transdisciplinary approaches and the establishment of intimate and long‐term partnerships with a range of community members. We examine four common modes of community engagement and explore how research projects are launched, who has the power in these relationships, and how projects evolve to become truly transformative for everyone involved. Plain Language Summary: GeoHealth research is often partnership focused. We describe four common models for community‐engaged GeoHealth research and highlight the central characteristics of each, while daylighting the lived experiences of LEAD Agency activists. We note a range of outcomes emerge which can foster science‐based environmental health policy making and lead to justice focused actions. Key Points: The GeoHealth research community often engages actively with civil society in the research enterprise, but often uses various models The models of engagement, from researcher‐heavy to community‐heavy, have very different outcomes A new model of training and support is required for the GeoHealth community to more productively engage with civil society